Axiological study of bone graft technology: Kajian aksiologi terhadap teknologi bone graft - Mardiana Adam; Eka Erwansyah; Rasmidar Samad; Burhanuddin Daeng Pasiga; Fuad Husain Akbar; Afriani (Makassar Dental Journal, 2022)
Objective: The use of bone graft technology is now quite widespread in the field of dentistry, for example in the application of dental implants in the oral cavity.This article aims to conduct an axiological study of bone graft technology in the regeneration of periodontal tissue. Methods: Literature study through review of relevant literatures by conducting articles searches using key-words. Result: Bone graft consists of several types with advantages and disadvantages of each in terms of usability. Bone graft has philosophical ethical values ​​in its use in human life. Conclusion: Technological advances in dentistry are the result of scien-tificdevelopment. Philosophical studies on axiological aspects show that bone graft is a technology that has been felt its benefits directly and affects human life. Bone damage will get a solution from this bone graft technology so that it can regain its pre-vious physical form, especially periodontal tissue repair.